(3GdQSGdI GdeMeOjIs - (3jhSa Hf CMeO Hf EHQGgje GdOQGRj GdHMQGfj, GHf oYrUoahQ,J (B1186 (3g` s ((3TjQGR s)
(3ChdgG (B:s
(3GcJH dg QSGdI JTJed Ydi LedI ef GMcGe GdejQGK s
(3BNQgG (B:s
(3hGddg SHMGfg CSFd Cf jhabfi ddYde hGdYed dLedI CMcGeg hCf jLfHfj GdNdd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B268s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B568s
Keywords: (3Yde GdaQGFVs